Factors Influencing Farmers’ Participation in Participatory Irrigation Management: A Comparative Study of two Irrigation Systems in Northern Areas of Pakistan - Alam, Arif; Kobayashi, Hajime; Matsumura, Ichizen; Esham, Mohamed; Siddighi, Faridullah; Siddighi, Balde Boubacar (Richtmann Publishing, 2012)
The purpose of this study was to understand how level of satisfaction with improved (IIS) and traditional irrigation systems(TIS) influences the level of participation in participatory irrigation management (PIM). Data was collected from 78 farmers selected bysystematic random sampling technique from two villages (Sultanabad and Parri) belonging to the IIS and TIS from Gilgit district in Gilgit-Batistan northern region of Pakistan. The descriptive analysis shows that four important variables such as adequacy of irrigation water,water availability on fixed turns and condition of present irrigation systems are main factors influencing satisfaction in IIS. However, levelof participation except at the main channel is not significantly different between the two systems. The indices of participation in the mainand field channels in the IIS are positive, while in the TIS these indices are negative which implies that the level of participation by theTIS farmers is low. Finally, by using regression analysis it is statistically confirmed that farmers’ satisfaction, family size, family labour,agricultural income and status of the irrigation system are significant factors influencing farmers` participation in PIM. Moreover, farmertraining and guidance provided to the IIS farmers by the NPIW through the WUAs also contribute to enhance the IIS farmers`participation in PIM. Therefore, strengthening of the institutional arrangements in both systems can enhance farmers` participation inPIM in Northern Areas of Pakistan.